Florida-Friendly Landscaping™ Pattern Book: Sample plant lists and designs for four Florida regions: USDA Hardiness Zone 9A, North Central Florida - Gail Hansen; Kelly Perez; Esen Momol (EDIS)
These pattern books were written by Gail Hansen, Kelly Perez, and Esen Momol and published by the UF Department of Environmental Horticulture, March 2011. They provide homeowners with design guidelines and suggested plants for typical residential site conditions in 4 USDA hardiness zones in Florida.